2022
DOI: 10.25122/jml-2022-0028
|View full text |Cite
|
Sign up to set email alerts
|

Diet, fibers, and probiotics for irritable bowel syndrome

Abstract: Many aspects make irritable bowel syndrome (IBS) challenging for both patients and physicians. The unclear pathogenesis with many pathways to be explored, bothering symptoms that affect the quality of life, and many subtypes of the condition are only a few reasons that make IBS difficult to control and obtain satisfactory results. Treatment options start with general advice for lifestyle, continue with non-pharmaceutical treatments, and finally touch classic treatments. In this review, pharmaceutical treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…Therefore, the increase in intestinal permeability could be caused by dyslipidemia, which increases zonulin levels and induces IBS. Fourth, diet has long been linked with IBS as a double-edged sword, it is a cause of diseases but also a treatment for symptom relief 37 . Some study suggested that gastrointestinal symptoms were frequently reported after intake of high-fat foods 38 40 , which can increase the level of plasma triglyceride 41 , 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the increase in intestinal permeability could be caused by dyslipidemia, which increases zonulin levels and induces IBS. Fourth, diet has long been linked with IBS as a double-edged sword, it is a cause of diseases but also a treatment for symptom relief 37 . Some study suggested that gastrointestinal symptoms were frequently reported after intake of high-fat foods 38 40 , which can increase the level of plasma triglyceride 41 , 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Several psychological therapies are effective for IBS, yet none is better. The most substantial body of research supports the effectiveness of CBT-based therapies and gut-directed hypnosis over the long run [ 28 ]. There is a significant prevalence of psychological comorbidity in IBS.…”
Section: Reviewmentioning
confidence: 99%
“…Management of IBS includes three directions (Figure 1): pharmacological therapy (antidepressants, antispasmodics, and laxatives), interventions on hygienic-dietary revitalisation [41][42][43], and psychotherapy (cognitive behavioural psychotherapy, dynamic psychotherapy, hypnotherapy, and biofeedback-assisted stress management intervention) [10,26,44]. During the previous ten years, there has been an increase in interest in changing the lifestyle and the hygienic dietary regimen, with patients opting for one of the following diets: LFD, gluten-free diet, low-fibre diet, low-carb diet, ketogenic diet, and palaeolithic diet [22,45,46].…”
Section: Therapeutic and Nutritional Managementmentioning
confidence: 99%
“…It improves global symptoms, abdominal pain, bloating, bowel water content, and QoL [47][48][49][50]. During the previous ten years, there has been an increase in interest in changing the lifestyle and the hygienic dietary regimen, with patients opting for one of the following diets: LFD, gluten-free diet, low-fibre diet, low-carb diet, ketogenic diet, and palaeolithic diet [22,45,46].…”
Section: Therapeutic and Nutritional Managementmentioning
confidence: 99%